MENGUNGKAP REALITAS DAN TANTANGAN KELAHIRAN PADA ANAK DI BAWAH UMUR: PERSPEKTIF KESEHATAN REPRODUKSI DAN SOSIAL - Nabila Siti Nurhasanah; Mirna Nur Alia Abdullah (Yayasan Literasi Sains Indonesia, 2025)
This research reveals the reality and challenges of underage childbirth in the city of Bandung from the perspectives of reproductive health and social well-being. The research methodology employed was a literature review, collecting relevant literature from various sources. The findings of the study indicate a concerning trend regarding underage marriages among women in Bandung. Early marriage for young women has negative consequences for their reproductive health and social welfare. Women who marry at a young age face a higher risk of pregnancy complications and premature childbirth. Furthermore, early marriage hinders girls' education and their opportunities to achieve economic independence, negatively impacting their personal and social development. In this context, comprehensive efforts are needed to prevent early marriages and protect the health and well-being of women. These efforts may involve inclusive sex education, raising public awareness, providing social support for at-risk girls, and strengthening regulations that prohibit underage marriages. In taking these steps, it is hoped that the rate of early marriages can be reduced, opening up opportunities for young women to grow and thrive in a healthy manner and attain their full potential in life.